A point mutation decouples the lipid transfer activities of microsomal triglyceride transfer protein - Wilson, Meredith H. (PLoS Genet, 2020)
Apolipoprotein B-containing lipoproteins (B-lps) are essential for the transport of hydrophobic dietary and endogenous lipids through the circulation in vertebrates. Zebrafish embryos produce large numbers of B-lps in the yolk syncytial layer (YSL) to move lipids from yolk to growing tissues. Disruptions in B-lp production perturb yolk morphology, readily allowing for visual identification of mutants with altered B-lp metabolism. Here we report the discovery of a missense mutation in microsomal triglyceride transfer protein (Mtp), a protein that is essential for B-lp production. This mutation of a conserved glycine residue to valine (zebrafish G863V, human G865V) reduces B-lp production and results in yolk opacity due to aberrant accumulation of cytoplasmic lipid droplets in the YSL. However, this phenotype is milder than that of the previously reported L475P stalactite (stl) mutation. MTP transfers lipids, including triglycerides and phospholipids, to apolipoprotein B in the ER for B-lp assembly. In vitro lipid transfer assays reveal that while both MTP mutations eliminate triglyceride transfer activity, the G863V mutant protein unexpectedly retains ~80% of phospholipid transfer activity. This residual phospholipid transfer activity of the G863V mttp mutant protein is sufficient to support the secretion of small B-lps, which prevents intestinal fat malabsorption and growth defects observed in the mttp(stl/stl) mutant zebrafish. Modeling based on the recent crystal structure of the heterodimeric human MTP complex suggests the G865V mutation may block triglyceride entry into the lipid-binding cavity. Together, these data argue that selective inhibition of MTP triglyceride transfer activity may be a feasible therapeutic approach to treat dyslipidemia and provide structural insight for drug design. These data also highlight the power of yolk transport studies to identify proteins critical for B-lp biology.